(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
The present paper describes and illustrates the Early Permian marine fauna collected from the northwest Himalaya (Lahul, India). Brachiopoda dominate the fauna in terms of abundance and include the two new species Tivertonia chumikensis and Neochonetes (Sommeriella) marpoensis. The Brachiopoda and Mollusca both exhibit strong Gondwanan relationships and the fauna belongs to the Cimmerian Province of Gondwana. Strong faunal links are shown with correlative faunas from Kashmir, Afghanistan and the Pamirs. Significant faunal relationships with correlative Western Australian faunas are also evident. The fauna is considered to be Late Sakmarian (Sterlitamakian) in age.